Cryospheric headwater genesis discrimination and social perception under megadrought and climate change scenarios: the Putaendo Valley case, Chile - Crespo, S. A.; Rybertt Goldammer, J.; Palmisano, T.; Lavergne, C.; Lo Vecchio, A.; Muñoz Gaete, L.; Fernandoy, F.; Vystavna, Y. (Frontiers in Earth Science, 2025)
The Putaendo watershed (Central Andes, Chile), notable for its pre-colonial history and as the first independent Chilean town (1817), also exhibits special hydrological features. It is one of the few areas in the Andes Cordillera where the inhabitants rely almost entirely on periglacial water sources. Since 2010, the region has also experienced a severe megadrought, drastically altering the water supply and straining the livelihoods of pastoralists and peasants to the limit. However, despite the significant decrease in precipitation recorded during the megadrought, water continued to flow from the headwaters to the Putaendo River. To elucidate the mechanisms behind this water persistence, we quantified the individual contributions of different water sources (snow, rock glaciers, and groundwater) within this basin through the analysis of stable water isotopes and major ions. The region’s simple winter precipitation regime, another crucial hydrological characteristic, further facilitates the clear discrimination and quantification of meltwater inputs distinct from precipitation using physicochemical tracers. Additionally, to comprehensively understand public knowledge regarding water origin, the impact of the megadrought and climate change, and the potential development of mega-mining projects (as this is the last basin without this activity in the Chilean Central Andes), we conducted a social perception analysis using a cross-sectional descriptive survey with non-probabilistic causal sampling. Upstream of the Chacrillas dam’s, where there is minimal human intervention, the river in this arid water cycle exhibited a marked predominance of water contributions from rock glaciers (56.1%), followed by groundwater (32.7%) and snow (11.2%). The inhabitants of the territory domonstrates a remarkable awareness and prior knowledge, with 45.5% of respondents identifying rock glaciers as the main source of water during dry years. There was also a clear negative public opinion regarding the developing of mega-mining projects in the valley (84.1%). Integrating these perceptions of water scarcity’s social complexities with an advanced understanding of water source contribution provides crucial information for regional water security management.